SIRT6 Protects Smooth Muscle Cells From Senescence and Reduces Atherosclerosis. Issue 4 (19th February 2021) - Grootaert, Mandy O.J.; Finigan, Alison; Figg, Nichola L.; Uryga, Anna K.; Bennett, Martin R.
Abstract : Rationale: Vascular smooth muscle cell (VSMC) senescence promotes atherosclerosis and features of plaque instability, in part, through lipid-mediated oxidative DNA damage and telomere dysfunction. SIRT6 (Sirtuin 6) is a nuclear deacetylase involved in DNA damage response signaling, inflammation, and metabolism; however, its role in regulating VSMC senescence and atherosclerosis is unclear. Objective: We examined SIRT6 expression in human VSMCs, the role, regulation, and downstream pathways activated by SIRT6, and how VSMC SIRT6 regulates atherogenesis. Methods and Results: SIRT6 protein, but not mRNA, expression was markedly reduced in VSMCs in human and mouse atherosclerotic plaques, and in human VSMCs derived from plaques or undergoing replicative or palmitate-induced senescence versus healthy aortic VSMCs. The ubiquitin ligase CHIP (C terminus of HSC70-interacting protein) promoted SIRT6 stability, but CHIP expression was reduced in human and mouse plaque VSMCs and by palmitate in a p38- and c-Jun N-terminal kinase-dependent manner. SIRT6 bound to telomeres, while SIRT6 inhibition using shRNA or a deacetylase-inactive mutant (SIRT6 H133Y ) shortened human VSMC lifespan and induced senescence, associated with telomeric H3K9 (histone H3 lysine 9) hyperacetylation and 53BP1 (p53 binding protein 1) binding, indicative of telomere damage. In contrast, SIRT6 overexpression preserved telomere integrity, delayed cellular senescence, and reduced inflammatory cytokine expression and changes in VSMC metabolism associated with senescence. SIRT6, but not SIRT6 H133Y, promoted proliferation and lifespan of mouse VSMCs, and prevented senescence-associated metabolic changes. ApoE −/− (apolipoprotein E) mice were generated that overexpress SIRT6 or SIRT6 H133Y in VSMCs only. SM22α-hSIRT6/ApoE −/− mice had reduced atherosclerosis, markers of senescence and inflammation compared with littermate controls, while plaques of SM22α-hSIRT6 H133Y /ApoE −/− mice showed increased features of plaque instability. Conclusions: SIRT6 protein expression is reduced in human and mouse plaque VSMCs and is positively regulated by CHIP. SIRT6 regulates telomere maintenance and VSMC lifespan and inhibits atherogenesis, all dependent on its deacetylase activity. Our data show that endogenous SIRT6 deacetylase is an important and unrecognized inhibitor of VSMC senescence and atherosclerosis. Abstract : Supplemental Digital Content is available in the text.